Implementation of Regional Public Service Agency (PPK-BLUD) Financial Management Patterns and Its Impact on Performance at the Regional General Hospital of Majene Regency - Nur Fadila; Safriansyah (AFEBI Accounting Review, 2022)
This study was conducted to determine the implementation of financial management patterns for regional public service agencies (PPK-BLUD) and their impact on performance. finance at the Regional General Hospital (RSUD) Majene Regency. This research uses descriptive qualitative method with the sampling technique using purposive sampling. The data collection method was done by interview and documentation techniques. The results of this study can be concluded that the implementation of the financial management pattern of regional public service agencies (PPK-BLUD) in the Majene District Hospital has mostly followed Permendagri regulation number 79 of 2018 concerning Regional Public Service Bodies so that it has an impact on improving financial performance.